Navigating E-Governance and ICT Dynamics in Afghanistan Higher Education - Nasrullah Rahimi; Asmatullah Rashidi; Musawer Hakimi; Mohammadullah Shirpoor (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the impact of E-Governance and ICT initiatives on higher education in Afghanistan. It aims to provide a comprehensive overview of the adoption and usage of electronic services, including scientific programs, student information storage, and service models. The study uses a mixed-methods approach, collecting data through questionnaires, interviews, and observations. Participants include professors, students, and technical staff from 17 universities in Afghanistan, ensuring diverse perspectives. The analysis reveals moderate adoption of electronic services, with a focus on scientific programs and student information management. Positive findings include the use of electronic systems for storing student information and active engagement in online conferences and financial processes. However, areas for improvement are identified, such as electronic evaluation and e-learning, suggesting the need for strategic enhancements. The Ministry of Higher Education demonstrates commendable integration of E-Governance initiatives, indicating progress in digital governance and ICT integration. The study's findings contribute to the existing literature on electronic services in higher education and offer recommendations for a more comprehensive and effective E-Governance framework